Analysis of Public – Private Partnership Model in Cooperation and Management of Sembilan Gili Beach Tourism, Genting, Sumenep District - Tini, Dwi Listia Rika; Alfiyah, Nur Inna (PT. Riset Press International, 2024)
The aim of this research is to describe the Public – Private Partnership model or collaboration between the public sector and the private sector in collaborating and managing Sembilan Beach Tourism. The cooperation model or Public Private Partnership in this research looks in more detail at each type which is seen from several provisions, namely: Asset Ownership, Operations and Management, Capital Investment, Commercial Risk, Duration of Collaboration, Need for technical expertise and managerial expertise, Need for Efficiency Operations, Large financial investments, Need for Political Commitment, Determination of Service Tariffs, Regulatory Framework, Information. The results of this research show that the Bringsang Village Government uses the Public-Private Partnerhip model in collaborating with the private sector. The variant used as the basis for cooperation is the BOT or Build-Operate-Transfer model which contains the simple meaning that this cooperation is related to development, management and at a predetermined time the authority to provide these services will be returned to the government. However, the reality on the ground turns out that there are several conditions of this cooperation model that are not fulfilled or even exceed the capacity of one of the parties in the cooperation for the development, development and management of Pantai Sembilan Tourism. However, apart from some discrepancies and also some adjustments to the characteristics and offers that might be taken into consideration by both parties, what needs to be noted is that this cooperation model can now be said to have succeeded in achieving its initial objectives. Agreement.